MULTICULTURAL APPROACH TO NOMADIC EDUCATION IN NIGERIA: IMPLICATIONS FOR SCHOOL ADMINISTRATION - Patrick, Oladunjoye (Sokoto Educational Review, 2018)
The paper examines the multicultural approach to nomadic education in Nigeria. It is evident from the data collected that cultured practices. Settlement pattern and language of instruction affect the effectiveness of nomadic education in Nigeria, 200 nomadic education teachers in 5 nomadic education centers were randomly selected from 5 geo-political zones in Nigeria. A 20 item questionnaire was drawn in line with the three research questions raised for the study, The data collected were analysed using the Mean [ x] and Standard Deviation [SD] methods. The study revealed that the cultural practices of nomads affect the effectiveness of nomadic education. The settlement pattern and language of instruction are also discovered to be major factors inhibiting the success of the nomadic education programme in Nigeria. The study recommends that school administrators should train teachers that can adapt to the settlement pattern of the nomads and the teaching and learning process must not be divorced from the cultural practices of the people and the language of instruction must be intelligible.